Money at the docks of tax havens: A guide - Shafik Hebous (Center for Economic Studies and ifo Institute (CESifo), 2011)
This essay critically revisits the roles and influences of tax havens in the world economy. It combines various massages of available studies in one scheme, documents a number of observations, and proposes several issues for future research.
Keywords: F23; H25; H32; 330; tax havens; tax avoidance; tax evasion; international taxation; corruption; offshore financial centres